A study on the relationship between organizational climate and organizational commitment - Yıldız, Yüksel (My University, 1993)
unknown
Keywords: Genel yönetim; ÖRGÜT İKLİMİ; ÖRGÜTE BAĞLILIK; Yürütmenin yönetimi